(untitled) (Journal of Bio-Science, 2024)
An efficient and reproducible in vitro regeneration process is required for the production of abiotic stress tolerance in rice through biotechnological approaches. In this study, optimization of culture media, callus induction and plant regeneration of five Aman rice varieties viz. BRRI dhan34, BRRI dhan51, BRRI dhan71, BRRI dhan79 and BRRI dhan95 were considered and mature seeds of those genotypes were collected from BRRI Reginald Station, Rajshahi. To investigate the effects of different concentration of 2,4-D and other PGRs on callus induction and regeneration some experiments were conducted and evaluated. Here, two basal media viz. MS and N6 were considered for this experiments out of four media (MS, B5, N6 and SK-3). It was observed that all five rice varieties showed higher callus induction on MS medium supplemented with 3.0 mg/l 2,4-D than other concentrations. On the basis of callus induction, data were recorded and BRRI dhan34, BRRI dhan51, BRRI dhan71, BRRI dhan79 and BRRI dhan95 gave 63.4%, 50.4%, 40.4%, 58% and 53% embryogenic calli respectively. In combination with BAP (2.0 mg/l), Kin (2.0 mg/l) and NAA (0.5 mg/l) supplemented with MS medium data showed better performance on regeneration. They can be used as a baseline for demand-driven in vitro rice propagation, providing useful information that can be combined with other agronomic features in rice development to improve the abiotic stress-tolerant cultivars through biotechnological methods in future. J. Bio-Sci. 32(1): 83-94, 2024